THE EFFECTS OF THE IMPLEMENTATION OF THE FAMILY OF HOPE PROGRAM POLICY ON THE QUALITY OF EDUCATION AND HEALTH SERVICE OF POOR FAMILY IN EAST JAKARTA - Raharjo, Paiman (UPI Press, 2015)
Family of Hope Program is established due to poor families low income in Indonesia who cannot fulfill their needs for health and education. This condition is often seen in the health care for poor pregnant women, affecting poor baby’s health and even baby’s mortality rate. Furthermore,there are still many poor families who cannot afford to provide their basic education needs due to the lack of budget. The focus of this research is to find the influence of Family of Hope Program policy on the quality of education and health service for poor families in East Jakarta.The purpose of this research is to gain information about the effect of policy implementation on the quality of education and health service of poor families. This research applies policy implementation model by Smith, with its four components: idealized policy, target group, implementing organization, and environmental factors. This research applied a quantitative approach using questionnaire, observation and interview. Data were analyzed with Structural Equation Modelling (SEM) and supported by observation and interview. The subjects of analysis in this research were the staffs of the Department of Social Affairs of East Jakarta sampled with the rules of thumb. The finding shows that the policy implementation of Family of Hope Program has significant effect on the quality of education and health service in East Jakarta.